Built the Effective Internal Control System in Local Governments of Developing Countries : A Case Study on Tegal City - Hadianto, Arief; V. Salomo, Roy; Panggabean, Maralus (International Journal of Engineering and Technology, 2018)
The purpose of this paper is to formulate the recommendation to reconstruction the Internal Control Policy in order to embody the Government Internal Control System, a specifically local government in Indonesia that is more effective. The research is using the qualitative method based on literature review and depth interview with a relevant source, including the top management of Tegal City and policy expertise as well. A policy analysis and Grindle theory are used to investigate the factors that contribute to the implementation of Government Regulation Number 60/2008 in uneffective Tegal City. The result shows that the reward and punishment in the policy is certainly needed, a derivative policy as an instrument to operate the must be applied policy, the rules regarding the local government officials should be revised, a professionalism strengthening and an independency of monitoring officials, the coordination and collaboration between local government to build a harmonization partnership in order to implement the policy that has to be improved, a dissemination policy and the integration of the internal control system report into a budgeting system and organization cultural development to create the better control environment in order heading to an effective internal control system.Â Â